Ultrastructure of mast cells and basophils - Dvorak, Ann M. (Chemical immunology and allergy, 2005)
Basophils and mast cells are similar but unique secretory cells which play a central role in inflammatory and immediate allergic reactions. In this book, the author reviews the ultrastructural studies of basophils and mast cells performed since the publication of an earlier monograph in 1991. These studies include the use of ultrastructural rules that allow identification of basophils and mast cells in new circumstances. The secretory granules and lipid bodies present in these cells are established as different, important organelles. A number of standard and newly developed ultrastructural imaging methods are described which define the subcellular locations of chymase, Charcot-Leyden crystal protein, histamine, and heparin as well as materials important in arachidonate and RNA metabolism, and in cytokine biology in basophils and mast cells. The findings presented elucidate new aspects of the secretory mechanisms of basophils and mast cells, their recovery, and the transepithelial route of passage of macromolecules stimulated by permeability mediators released from these cells. Including more than 180 excellent micrographs, this book will be of special interest to basic scientists in immunology, cell biology, secretion and angiogenesis research, and histochemistry. As mast cells and basophils play a crucial role in various diseases, it will be essential reading for allergists, immunologists, dermatologists, hematologists, gastroenterologists, rheumatologists, neurologists, pathologists, pulmonologists, and cardiologists